Strategic Recovery and Resource Regeneration in Russian State Corporations: Pemulihan Strategis dan Regenerasi Sumber Daya di Perusahaan Negara Rusia - Mamarajabov Farhod Bakhtiyarovich (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: State-owned corporations are fundamental pillars of Russia’s strategic and economic landscape. Specific Background: Entities such as Rosatom, RZD, Rostec, and Rosneft operate in volatile environments where state intervention intersects with global pressures and institutional legacies. Knowledge Gap: While crisis management in private firms is extensively studied, there is limited understanding of how Russian public-sector corporations regenerate resources—financial, technological, and human—amid persistent crises. Aim: This study investigates the mechanisms of crisis response and resource reproduction in leading Russian state corporations through comparative case analysis. Results: Findings indicate that effective crisis management integrates external support with internal capacities—strategic innovation, managerial reform, and market diversification—enabling sustained resilience beyond temporary relief. Novelty: Unlike previous studies that treat crises as episodic disruptions, this research conceptualizes them as cyclical phenomena requiring embedded reproduction strategies. Implications: The study underscores the need for institutionalized crisis planning, conditional state aid linked to reforms, and long-term investments in innovation and workforce retention to enhance resilience and strategic autonomy in state-led economies.Highlight : Resilience Depends on Internal StrategyLong-term survival of Russian state corporations relies more on internal reforms and innovation than on external state support. Diversification is CrucialExpanding markets, funding sources, and operations reduces crisis vulnerability and enhances corporate stability. Leadership and Governance MatterEffective crisis responses often coincide with leadership changes, improved transparency, and stronger corporate governance Keywords : Crisis Management, Resource Reproduction, Russian State Corporations, Strategic Planning, Innovation